Pengaruh Struktur Modal dan Return On Investment terhadap Nilai Perusahaan Subsektor Perkebunan yang Terdaftar di Bursa Efek Indonesia - Wahyu Indah Mursalini; Nurhayati Nurhayati; Rahmi Rahmadani (BADAN PENERBIT STIEPARI PRESS, 2026)
This research seeks to investigate how Capital Structure and Return On Investment impact Company Value in manufacturing companies within the Plantation sub-sector that are listed on the Indonesia Stock Exchange. The sample for this research consisted of 15 plantation sub-sector firms selected using a purposive sampling approach. The findings reveal that Capital Structure significantly affects Company Value among Plantation sub-sector Manufacturing Companies on the Indonesia Stock Exchange, indicated by a t-value of 31.346 and a significance level of 0.000. Additionally, Return On Investment also has a significant impact on Company Value in these firms, with a t-value of 7.032 and a significance level of 0.000. When assessed together, both factors collectively influence Company Value, as shown by an F-value of 521.457 and a significance level of 0.000. The coefficient of determination (R²) shows that 97% of the changes in firm value are due to Capital Structure and Return on Investment, while the remaining 3% is influenced by other factors not included in this regression model. In light of these findings, the study recommends that companies effectively manage their capital structure and enhance ROI to better attract investor interest and improve their firm value.